2023
DOI: 10.5194/acp-23-4819-2023
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Arctic clouds modelled with the Unified Model and Integrated Forecasting System

Abstract: Abstract. By synthesising remote-sensing measurements made in the central Arctic into a model-gridded Cloudnet cloud product, we evaluate how well the Met Office Unified Model (UM) and the European Centre for Medium-Range Weather Forecasting (ECMWF) Integrated Forecasting System (IFS) capture Arctic clouds and their associated interactions with the surface energy balance and the thermodynamic structure of the lower troposphere. This evaluation was conducted using a 4-week observation period from the Arctic Oce… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 60 publications
2
5
0
Order By: Relevance
“…In all MCAO stages, ERA5 significantly over-estimates the amount of liquid water present in the clouds. A similar enhanced abundance of liquid-bearing clouds especially over sea ice has been reported for the IFS, the model behind ERA5 (Tjernström et al, 2021;McCusker et al, 2023). In the MCAO case here, this is in contrast to CARRA (Figure 9c).…”
Section: Cloud Propertiessupporting
confidence: 83%
See 2 more Smart Citations
“…In all MCAO stages, ERA5 significantly over-estimates the amount of liquid water present in the clouds. A similar enhanced abundance of liquid-bearing clouds especially over sea ice has been reported for the IFS, the model behind ERA5 (Tjernström et al, 2021;McCusker et al, 2023). In the MCAO case here, this is in contrast to CARRA (Figure 9c).…”
Section: Cloud Propertiessupporting
confidence: 83%
“…The ERA5 clouds systematically precipitate stronger over the MIZ and ocean than clouds in CARRA (Figure A8e). The significance of our findings is reinforced by McCusker et al (2023), who showed that issues such as an over-abundance of low, liquid-bearing clouds can propagate into higher-resolution models through large-scale forcings.…”
Section: Cloud Propertiessupporting
confidence: 57%
See 1 more Smart Citation
“…For example, errors with respect to the vertical distribution of liquid and ice, and especially the representation of thin supercooled liquid layers within mixed-phase clouds, can induce radiative biases (Gilbert et al, 2020;Vignon et al, 2021;Inoue et al, 2021). In addition to microphysics, model cloud macrophysical parameterisations, especially relating to cloud fraction, may impact cloud radiative effects (Van Weverberg et al, 2023;McCusker et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Models often cannot reproduce cloud-free conditions when the aerosol particle (and thus CCN) concentrations are low in the region Stevens et al, 2018). Many models have simplified microphysical schemes and, for example, assume constant droplet number or aerosol concentrations (Wesslén et al, 2014;Bulatovic et al, 2019;McCusker et al, 2023).…”
Section: Introductionmentioning
confidence: 99%